The Effects of the New Therapeutic Treatments for Diabetes Mellitus on the Male Reproductive Axis - Pelusi, Carla (Frontiers in Endocrinology, 2022)
One of the complications of chronic hyperglycemia and insulin resistance due to type 2 diabetes mellitus (T2DM) on the hypothalamic-pituitary-gonadal axis in men, is the high prevalence of hypogonadotropic hypogonadism, which has been recently defined as functional hypogonadism, characterized by low testosterone associated with inappropriately normal gonadotropin levels. Although the pathophysiology of this hormonal imbalance may be related to several factors, including glycemic control, concomitant sleep apnea, insulin resistance, the main role is determined by the degree of central or visceral obesity and the consequent inflammatory state. Several drugs have been developed to treat T2DM such as glucagon-like peptide-1 receptor agonists, dipeptidyl peptidase 4 inhibitors, and sodium-glucose co-transporter 2 inhibitors. All appear to be effective in ameliorating blood glucose control, by lowering inflammation and body weight, and most seem to reduce the risk of micro- and macrovascular damage as a consequence of uncontrolled diabetes. A few studies have evaluated the impact of these drugs on gonadal function in T2DM patients with hypogonadism, with promising results. This review summarizes the main current knowledge of the effects of these new antidiabetic drugs on the hypothalamus–pituitary–gonadal axis ,showing their potential future application in addition to glucose control in dysmetabolic male patients.